Redução de sódio em alimentos: uma análise na perspectiva do comportamento do consumidor - Gonçalves, Carla Saraiva (2017)
Great efforts have been made to reduce sodium intake due to its positive correlation with disease incidence. Understanding consumer behavior is one way to achieve this. The general objective of this workwas to generate information about the behavior of consumers in relation to reduction in sodium consumption through the techniques of educational intervention, focus group and joint analysis of factors. The effectiveness of different forms of educational intervention was compared in relation to the improvement of consumers' knowledge about sodium and also on the label of products processed with sodium reduction. Three different educational interventions were used: active learning (AL), passive learning (PL) and passive learning with authority effect (PA). Each intervention had a soft and aggressive approach. The volunteers were submitted to one of six interventions. The joint analysis was used to evaluate the influence of three independent variables on consumers' intention to buy processed products with sodium reduction. Through the focus group, three factors were selected for the preparation of the labels: product (pepperoni, frescal cheese and parmesan cheese), claims (25% less sodium, less sodium and light), color (blue, green, red). Nine label images were presented to 745 consumers, who were asked to evaluate the purchase intent of each of them. Educational interventions were equally effective in understanding participants' objective questions about sodium and the label. Forsubjective questions, which refer to participants' behavior and purchase intent, AP's educational intervention was slightly better than the others. The aggressiveapproach proved to be more efficient compared to the soft approach. Educational intervention has played an effective role in improving consumer understanding of the damage caused by excessive sodium intake. Through the joint analysis, it was verified that the purchase was intentionally affected by the claims, type of product and color of the label. The groups with the highest relative importance for the claims were the groups formed by men (active and sedentary). The claim "25% less sodium", the product "frescal cheese" and the "blue" color had a greater impact on the intention of purchase for most of the evaluated groups. The claim "light", product "parmesan cheese" and the "red" color had a minor impact on the purchase intention for all groups evaluated.